Understanding of Legal Reform on Sociology of Islamic Law: Its Relevance to Islamic Family Law in Indonesia - Zayyadi, Ahmad; Ridwan; Hidayat, Arif; Ubaidillah; Masuwd, Mowafg Abrahem (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2023)
This article analyses the understanding of legal modernization in the sociology of Islamic law in Muslim countries regarding Islamic family law in Indonesia. The theory of legal modernization arises from the long history of Islamic legal theory since the Dutch era related to the enactment of Islamic law, both in terms of the struggle between customary law, Islamic law, and state law. The work for the emergence of legal theories such as Receptie theory becomes a filter for Islamic law in its application to Muslim communities in Indonesia. The results of this study indicate that the modernization of law in the form of KHI applies to the Indonesian Muslim community and requires the nation to be more mature in responding to modernity. However, there is an intersection between modernization and legal secularisation in the Islamic world, such as in Turkey, Egypt, Sudan, and Syria. Legal modernization from fiqh towards positivisation has given birth to formulations in Islamic family law in the form of sociological dynamics in contemporary Indonesian Islamic society.